2010
DOI: 10.1111/j.1574-6968.2010.01971.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative thymidylate synthase, ThyX, involved in Corynebacterium glutamicum ATCC 13032 survival during stationary growth phase

Abstract: A BLASTP search has shown the presence of a gene homologous to an alternative thymidylate synthase (TS), thyX, in Corynebacterium glutamicum ATCC 13032. To determine if thyX is functionally analogous to thyA, thyX was cloned in a plasmid and the resulting construct was transferred by transformation into a thyA mutant of Escherichia coli. The ThyX from C. glutamicum compensated for the defect in TS-deficient E. coli. A functional knockout of the thyX gene was constructed by allelic replacement using a sucrose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Earlier studies have indeed questioned whether the true biological substrates of ThyX have been identified, as many of these enzymes (including ThyX from M. tuberculosis and C. glutamicum ) have very low TS catalytic activity (Agrawal et al , 2004; Hunter et al , 2008; Kan et al , 2010). It should be noted that thyX from C. glutamicum is only thought to be essential upon reaching stationary phase (Park et al , 2010), and so the biological roles of ThyX appear to differ between these two relatively closely related species. Importantly, we have shown that this enzyme is a plausible tuberculosis drug target, and our collaborators have recently published their findings that compounds specifically designed to inhibit M. tuberculosis ThyX are effective, with no activity against ThyA (Kögler et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have indeed questioned whether the true biological substrates of ThyX have been identified, as many of these enzymes (including ThyX from M. tuberculosis and C. glutamicum ) have very low TS catalytic activity (Agrawal et al , 2004; Hunter et al , 2008; Kan et al , 2010). It should be noted that thyX from C. glutamicum is only thought to be essential upon reaching stationary phase (Park et al , 2010), and so the biological roles of ThyX appear to differ between these two relatively closely related species. Importantly, we have shown that this enzyme is a plausible tuberculosis drug target, and our collaborators have recently published their findings that compounds specifically designed to inhibit M. tuberculosis ThyX are effective, with no activity against ThyA (Kögler et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that both thyA and thyX from M. tuberculosis (Rengarajan et al , 2004; Sampathkumar et al , 2005) and Corynebacterium glutamicum (Park et al , 2010) can functionally complement an E. coli thyA deletion strain. ThyA and ThyX from these two species exhibit 72 and 63 % sequence similarity at the amino acid level, respectively (Kan et al , 2010; Park et al , 2010). Both M. tuberculosis ThyA and ThyX proteins have been shown to have TS activity in vitro , with ThyA being substantially more efficient than ThyX (Hunter et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium strains are peculiar due to the presence of both thyX and thyA genes, but even in this case, thyX has been shown to code for essential cellular function(s) [24]. Moreover, in other Corynebacteriaceae, ThyX proteins have been specifically implicated in survival during the stationary growth phase [25]. …”
Section: Introductionmentioning
confidence: 99%
“…This could be because both ThyA and ThyX contribute to the synthesis of the one‐carbon unit for the biosynthesis of thymidine in C. glutamicum . Moreover, because only the ΔthyX strain exhibited poor survival during the stationary growth phase, it has been suggested that the expression levels of thyA and thyX differ in response to different growth conditions (Fivian‐Hughes et al ., ; Park et al ., ).…”
Section: Introductionmentioning
confidence: 97%